Phytochemical Profile and Antimicrobial Activity of Aqueous Garlic Extract (Allium sativum L.) for Food Preservation - Torres, Elmer (2024)
The contamination of seafood by common bacteria and the ecological limitations of antibacterials has prompted the investigation of the phytochemical profile and antimicrobial activity of aqueous garlic extract (Allium sativum L.) against four significant food-associated pathogens: Salmonella typhi, Micrococcus luteus, Staphylococcus aureus, and Escherichia coli. Absorbance curves were constructed, inhibition halos were measured, and minimum lethal concentrations were determined. This study aims to harness the properties of garlic and its derivatives, making them ideal for use in pharmaceutical and industrial products. The results showed greater inhibitory activity against Gram-positive bacteria compared to Gram-negative bacteria. Specifically, a concentration of 0.125 g/ml of the extract produced inhibition halos with diameters of 0.75 mm for S. typhi, 0.8 mm for M. luteus, 11 mm for S. aureus, and 8.25 mm for E. coli. Furthermore, a concentration of 1.0 g/ml of the extract exhibited bactericidal activity at 210 minutes against M. luteus, 330 minutes against S. typhi, and 270 minutes against S. aureus, but it showed no such effect against E. coli.